Anticipating Resistance to Health Advice: A Speech Act Perspective. Issue 3 (3rd April 2019) - van Poppel, Lotte
ABSTRACT: This article addresses the problem of resistance to health advice. It is argued that potential criticism against advice in health settings can be systematically defined with the help of the felicity conditions of the speech act of advising. By taking into account the setting in which health advice is delivered, specified conditions for advising in health settings are proposed. The objective of this study is to present a systematic overview of relevant criticism showing what issues could provoke resistance to advice and thus need to be anticipated or answered. The relevance of these points is illustrated in a case study of advice on achieving a healthy weight on webpages from the U.S. Centers for Disease Control and Prevention. A content analysis of the webpages shows that each of the possible points of criticism can be dealt with to prevent resistance.